Pengaruh Pengetahuan Kewirausahaan, Efikasi Diri, Karakter Wirausaha dan Literasi Digital Terhadap Minat Berwirausaha Menggunakan E-Commerce (Mahasiswa Aktif Perguruan Tinggi di Kota Malang) - Ngatiningsih, Tuti Khoiriyah; Mardani, Ronny Malavia; Bastomi, Mohammad (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to test and explain the influence of entrepreneurial knowledge, self-efficacy, entrepreneurial character, and digital literacy on interest in entrepreneurship using e-commerce among active university students in Malang City. The sample used in this research was 90 respondents using purposive sampling technique. The data analysis method used in this research is quantitative data analysis using multiple linear regression analysis. The data test used is partial hypothesis testing (t test). The results of this research show that partially (t test) the entrepreneurial knowledge variable has a significant effect on interest in entrepreneurship using e-commerce among active university students in Malang City, the self-efficacy variable has no significant effect on interest in entrepreneurship using e-commerce among active university students in Malang City, the entrepreneurial character variable has a significant effect on interest in entrepreneurship using e-commerce among active university students in Malang City and the digital literacy variable has a significant effect on interest in entrepreneurship using e-commerce among active university students in Malang City. Keywords: Entrepreneurship Knowledge, Self-Efficacy, Entrepreneurial Character and Digital Literacy